Transformation from D022 to L12 in Al3Ti by Fe Addition for Enhanced Wear Resistance - Guijiang Diao; Junfeng Yuan; Anqiang He; Dong Zhang; Aakash Kumar; Ranran Fang; Anatoliy Vorobyev; Wengang Chen; Dongyang Li (Lubricants)
The addition of third elements may help transform brittle D022-structured lightweight Al3Ti to a relatively ductile L12-structured (Al, M)3Ti (where M represents the third elements), thus increasing the ductility at the expense of hardness. Such a transformation could benefit the wear resistance of the alloy due to improved toughness if a proper balance between the hardness and ductility is achieved. In this work, a D022-predominant Al3Ti alloy (S-Al3Ti) and an L12-predominant (Al, Fe)3Ti alloy (S-Al67Ti25Fe8) were fabricated by arc melting. Change in wear resistance, corresponding to a D022-to-L12 transformation, caused by the addition of Fe as a representative third element, was investigated and compared with the wear resistance of a commercial Al-matrix composite reinforced by 30 wt.% SiC particles (S-Al/SiCp) as a reference material. It was observed that wear of the S-Al3Ti resulted from abrasion involving synergistic oxidation, leading to a larger volume loss. In contrast, the softer S-Al67Ti25Fe8 showed enhanced wear resistance, benefiting from improved toughness with reasonable hardness. During the wear testing, both the alloys exhibited better performance than S-Al/SiCp, a well-known lightweight composite. This study highlights that D022-to-L12 transformation enhances wear resistance due to increased toughness which can be adjusted using the addition of a third element.